Effect of end-expiratory carbon dioxide monitoring on painless colonoscopy procedures in obstructive sleep apnea patients - Pengxia Wang; Qiuxiang Jiang; Kaihui Li; Yinying Zeng; Zhangxing Chen; Shanshan Liu (Perioperative Medicine)
Abstract Background Carbon dioxide (CO2) accumulation during prolonged painless colonoscopy procedures in patients with obstructive sleep apnea syndrome (OSAS) can lead to an increased incidence of various complications. The disposable end-expiratory CO2 device monitors the respiratory function and CO2 elimination of patients in real time, providing timely feedback to physicians. This enhances the safety and success of the procedure and improves the overall medical experience for the patient. Method A total of 158 patients with OSAS underwent colonoscopy and were divided into two groups. The study group received end-expiratory CO2 monitoring, while the control group underwent routine monitoring. Perioperative interventions, patient satisfaction, and postoperative complications were compared between the two groups using a case–control method. All colonoscopic procedures were performed by surgeons. Result The study group exhibited a lower incidence of hypoxemia and higher utilization of upper airway ventilation devices, resulting in greater postoperative satisfaction (P = 0.019, P = 0.002, P < 0.001, respectively). Conversely, the control group experienced a higher incidence of postoperative nausea and vomiting as well as abdominal pain and abdominal distension (P = 0.006, P = 0.038, P < 0.012). Conclusion Employing disposable end-expiratory CO2 monitoring during painless enteroscopic procedures in patients with OSAS reduces the incidence of hypoxemia, enhances postoperative satisfaction, and decreases the incidence of postoperative complications. Trial registration number ChiCTR2400083702; Registration date: April 2024.